A Study of the Digital Transformation and Efficiency Improvement Path of University Administration - Zhang Yiyan (SHS Web of Conferences)
The digital transformation of the administration of colleges and universities is an important way to improve their management efficiency and quality. Due to the fast evolution of information technology, including the extensive use of emerging technologies like big data, cloud computing, and artificial intelligence, colleges, and universities must enhance the digital transformation of administrative operations to achieve process optimization, informed decision-making, and enhanced service capabilities. This study aims to determine the effective path of digital transformation and efficiency improvement of the administration of colleges and universities. Universities are encouraged to develop comprehensive strategic plans for digital transformation, clearly outlining the goals, paths, and methods of digital transformation and ensuring the systematic and long-term effectiveness of the plans. Second, strengthening the construction of an information platform is the foundation for realizing the digital transformation of administrative management. Colleges and universities should input the required resources to develop a comprehensive management platform integrating data processing, information exchange, and resource sharing. As a result, they are conducive to supporting efficient information exchange and resource integration. Additionally, it is necessary to improve the data governance mechanism in colleges and universities to ensure the safety and accuracy of data, providing reliable support for scientific decision-making.